1994
DOI: 10.1159/000163882
|View full text |Cite
|
Sign up to set email alerts
|

Hormone-Regulated Genes (pS2, PIP, FAS) in Breast Cancer and Nontumoral Mammary Tissue

Abstract: Expression of the hormone-regulated genes, pS2, prolactin-inducible protein (PIP) and fatty acid synthetase (FAS), was investigated by Northern blotting in primary breast carcinoma, metastatic breast cancer in axillary lymph nodes, in uninvolved breast tissue from mastectomies and in normal lymph nodes. There were considerable differences in expression of the genes between the tissues. The proportion of tissues containing PIP-mRNA decreased from uninvolved breast tissue to primary breast carcinoma to metastati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0

Year Published

1996
1996
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…The TIMP1 and TFF1 genes that were chosen for in-depth characterization are overexpressed in breast cancer, making them promising prognostic markers (Hahnel et al, 1994;Toi et al, 1998;Balleine and Clarke, 1999;Fata et al, 2004). In addition, expression of both genes may be regulated by the breast cancer tumor suppressor BRCA1.…”
Section: Discussionmentioning
confidence: 99%
“…The TIMP1 and TFF1 genes that were chosen for in-depth characterization are overexpressed in breast cancer, making them promising prognostic markers (Hahnel et al, 1994;Toi et al, 1998;Balleine and Clarke, 1999;Fata et al, 2004). In addition, expression of both genes may be regulated by the breast cancer tumor suppressor BRCA1.…”
Section: Discussionmentioning
confidence: 99%
“…In the literature, directly acted-out autodestructive behaviour is distinguished, both nosologically and terminologically, from the disorder complex ‘factitious disorders’ [2, 37, 38]. ‘Medical cases of unclear genesis’ are placed along a continuum of ‘factitious pathological behaviour’.…”
Section: Aetiology Pathology and Pathogenesismentioning
confidence: 99%
“…Direct autodestructive behaviour, which is initiated by a sense of tension and acted out to achieve a reduction in tension, and is therefore not to be grasped in the framework of a personality disorder, is also referred to in the literature as ‘overt self-harm’ [13, 25,][38]. Impulse control, affect regulation and dissociative disorders are described in the same context.…”
Section: Aetiology Pathology and Pathogenesismentioning
confidence: 99%
“…Therefore, the most spatially dysregulated PIP could be considered the most sensitive spatial protein biomarker for hormonally triggered cytoskeleton remodeling. PIP may prove particularly valuable for screening breast regions where biochemical processes (including cancer) were triggered by hormonal action 50 – 54 . Our functional study in KM plotter has proven that there might be a link between PIP and BC, as it has shown that high expression of PIP at protein level in BC patients ( N = 126) leads to significantly lower overall survival ( p = 0.054) compared to BC patients with low PIP expression within a timeline of 120 months post-diagnosis (Supplementary Fig.…”
Section: Discussionmentioning
confidence: 99%